Nonpoint-source pollution control and greening of China’s agrifood systems - Gong, Binlei; Chen, Kevin Z.; Fang, Xiangming; Meng, Ting; Zhou, Li; Shi, Minjun; Wang, Shuo (2021)
The unsustainable agricultural production mode of “high input and high output” has imposed a heavy burden on China’s ecosystems, and severely restricted the sustainable development of the country’s agrifood systems. Taking long-term prevention and control of agricultural nonpoint-source pollution as the key approach can play an important role in upgrading country’s agriculture to circular and renewable agriculture-food-ecological system circulation. Currently, the five major sources of agricultural nonpoint-source pollution in China are livestock, poultry and aquaculture; chemical fertilizers; pesticides; crop residues; and waste plastic films. The Chinese government has issued corresponding policies and measures to carry out prevention and control at the source and end, which have achieved initial results. Its accurate grasp of direction and implementation provide lessons for other developing countries. Several years of treatments have resulted in remarkable reduction of nitrogen and phosphorus emissions from the livestock and poultry farming, but the pollutant emissions of the aquaculture are increasing, and the utilization rate of chemical fertilizers and pesticides is still relatively low compared with that of developed countries. China mainly relies on policies and legal means, and government subsidies to control agricultural nonpointsource pollution in the short term. However, more emerging options should be explored to establish a long-term mechanism to prevent and control agricultural nonpoint-source pollution and to transform the agrifood systems to become even greener, including property rights arrangements, interprovincial ecological compensation, green finance, and brand building for ecological agricultural products.